POLITIK PENDIDIKAN AGAMA DAN PERUBAHAN PRILAKU DI SUMATERA BARAT - Salim, Delmus Puneri; Kryati, Lies (El -Hekam, 2017)
This paper demonstrates how the Islamic education has been used to reflect social problems in the region. The paper argues that decadency and the use of drugs and other social problems has enabled the regional governments to engage in Islamic education. The paper suggests that the involvement was driven by the capacity to reduce fears of social problems in the society. It also argues that the other mechanism to solve social problems are overlooked as the paper presents availability of jobs concerning at customers’ satisfaction would overcome social problems.